2016
DOI: 10.3945/ajcn.115.117770
|View full text |Cite
|
Sign up to set email alerts
|

Mineral- and vitamin-enhanced micronutrient powder reduces stunting in full-term low-birth-weight infants receiving nutrition, health, and hygiene education: a 2 × 2 factorial, cluster-randomized trial in Bangladesh

Abstract: The use of a mineral- and vitamin-enhanced MNP significantly reduced stunting in FT-LBW infants in this high-risk setting. The use of a water-based HS did not have an additive effect. This trial was registered at clinicaltrials.gov as NCT01455636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 37 publications
2
42
1
5
Order By: Relevance
“…This has important policy implications because MNP distribution is being scaled-up nationally in Bangladesh and in other countries (5), mainly to reduce anemia. Although enhanced formulations of MNPs with 22 micronutrients may promote growth in low-birth-weight infants (37), their efficacy and effectiveness for the general population of infants have not been tested. It should be noted that postnatal growth faltering in the RDNS and other studies (34,36) was still evident (although reduced) despite the provision of fortified supplements, pointing to the need for more comprehensive interventions that target the multiple causes of poor growth, including both prenatal and postnatal infections (2).…”
Section: Postnatal Growth Ratementioning
confidence: 99%
“…This has important policy implications because MNP distribution is being scaled-up nationally in Bangladesh and in other countries (5), mainly to reduce anemia. Although enhanced formulations of MNPs with 22 micronutrients may promote growth in low-birth-weight infants (37), their efficacy and effectiveness for the general population of infants have not been tested. It should be noted that postnatal growth faltering in the RDNS and other studies (34,36) was still evident (although reduced) despite the provision of fortified supplements, pointing to the need for more comprehensive interventions that target the multiple causes of poor growth, including both prenatal and postnatal infections (2).…”
Section: Postnatal Growth Ratementioning
confidence: 99%
“…With these formulations, we found a positive impact on stunting apparent at 1 mo and a larger impact at 24 mo of age in the group that received MNP and no effect in the group that received LNS. A recent study from Bangladesh that provided MNP to full-term, low birth weight children 6–12 mo of age in conjunction with general nutrition, health, and hygiene education (but not family ration) also demonstrated a significant impact on reducing stunting (OR = 0.35 at 12 mo) (11). The MNP formulation for the Bangladesh study included 22 micronutrients, many with identical or nearly identical concentrations as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies with randomized controlled design, which combined using only MNP as intervention are mixed. A positive effect on linear growth was found in some trials (Adu-Afarwuah et al, 2007;Shafique et al, 2016;Soofi et al, 2013), whereas no difference between intervention and control children was observed in other studies (Bilukha, Howard, Wilkinson, Bamrah, & Husain, 2011;Giovannini et al, 2006;Lemaire et al, 2011;Macharia-Mutie et al, 2012;Osei et al, 2010). Moreover, two systematics reviews conducted in 2013 concluded no significant effects on growth assessed by mean z scores (De-Regil et al, 2013;Salam et al, 2013) and prevalence of stunting and wasting (Salam et al, 2013).…”
Section: Anthropometrymentioning
confidence: 97%
“…Therefore, improved feeding practises were not be translated into linear growth outcomes as suggested by findings of several other studies that provided nutrition education on complementary feeding (Negash et al, 2014;Owais et al, 2016;Schroeder et al, 2002;Zhang et al, 2016). On the other hand, a positive effect on growth has been reported in two randomized controlled trials with prospective follow-up of young children in Pakistan (Soofi et al, 2013) and Bangladesh (Shafique et al, 2016).…”
Section: Anthropometrymentioning
confidence: 99%